2022
DOI: 10.1002/cjoc.202100498
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hyperbranched Polythioamides Synthesized from Catalyst‐free Multicomponent Polymerization of Elemental Sulfur

Abstract: Hyperbranched polymers with unique topological structures, large number of branching sites and terminal groups have attracted much attention, and are expected to possess advanced functionalities compared with their linear polymer counterparts. The development of hyperbranched polymers is hence highly desired but challenging, especially for sulfur-containing polymers which are attractive metal absorbents, optical materials, dielectric materials, and self-healing materials. In this work, six hyperbranched polyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…12–14 Considering that elemental sulfur is an abundantly existing industrial byproduct whose profitable utilization is a global concern, 15 a series of elemental sulfur-based multicomponent polymerizations were developed to directly convert elemental sulfur to sulfur-containing functional polymers such as polythioamides and polythioureas. 2–4,16–20 For example, the MCP of sulfur, aliphatic diamines, and aromatic dialdehydes was first reported by Kanbara et al to afford aliphatic polythioamides at 115 °C in DMAc; 17,18 later, we reported a catalyst-free MCP of sulfur, aliphatic diamines, and aromatic diynes to produce seven aliphatic polythioamides with 100% atom economy at 100 °C in pyridine. 4 A series of hyperbranched polythioamides with various topological structures, well-characterized chemical structures, and good solubility were also synthesized through these MCPs.…”
Section: Introductionmentioning
confidence: 74%
“…12–14 Considering that elemental sulfur is an abundantly existing industrial byproduct whose profitable utilization is a global concern, 15 a series of elemental sulfur-based multicomponent polymerizations were developed to directly convert elemental sulfur to sulfur-containing functional polymers such as polythioamides and polythioureas. 2–4,16–20 For example, the MCP of sulfur, aliphatic diamines, and aromatic dialdehydes was first reported by Kanbara et al to afford aliphatic polythioamides at 115 °C in DMAc; 17,18 later, we reported a catalyst-free MCP of sulfur, aliphatic diamines, and aromatic diynes to produce seven aliphatic polythioamides with 100% atom economy at 100 °C in pyridine. 4 A series of hyperbranched polythioamides with various topological structures, well-characterized chemical structures, and good solubility were also synthesized through these MCPs.…”
Section: Introductionmentioning
confidence: 74%
“…As the use of polymers becomes more widespread and their applications get broader, a wider range of specific properties are required, such as electrical conductivity, photosensitivity, magnetism, and self-healing. [1][2][3][4][5][6][7][8][9][10] As a result, studying the functionalization of polymers is crucial. After long-term development, research on the functionalization of polymers has gradually matured.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1‐3 ] Although the alkyne‐based polymerizations are rarely described in the textbooks, plenty of polymers with diverse structures and versatile functionalities can be synthesized and derived from alkyne monomers, attracting avid attention from different academic research communities such as polymer chemistry, biochemistry, materials science, and so on. [ 4‐14 ] Nevertheless, alkyne‐based polymerizations are still limited in applications and confront challenges to some extent, owing to the poor reactivity of the ethynyl groups. Thus, much effort has been devoted to improving the reactivity of alkynes by adjacently connecting electron‐withdrawing groups, which are colloquially termed as the activated alkynes.…”
Section: Introductionmentioning
confidence: 99%